The primary roots of Sorghum bicolor as a model to study the mechanisms related to mixed-linkage glucan hydrolysis during the aerenchyma development - Teixeira, Bruno Rubens Flausino (2021)
Sorghum bicolor is one of the most important worldwide cereal crops due to its high carbon fixation efficiency, nitrogen acquisition, great adaptability to grow in distinct environments, and, above all, used as a staple food in Africa and Asia. Sorghum germplasm collection, quality of sequenced genome, and recent advances on genetic transformation have set this species as an up-and-coming model among C4 grasses. Sorghum, like all grasses, is made up of type II cell wall, whose main feature is the significant amounts of arabinoxylan and mixed-linkage (1,3;1,4)-β-D- glucan (MLG) polysaccharides. MLG is a D-glucose hemicellulosic polymer whose linear chain holds mainly β-(1,4) glycosidic linkages intercalated with little β-(1,3) glycosidic linkages that kink the chain turning it into a more water-soluble polymer. As a result, MLG chemical properties are attractive for biotechnology then understanding MLG synthesis and hydrolysis are essential topics. \"Lichenases,\" technically known as endo-β-D-(1,3;1,4)-glucanases, specifically hydrolyze β(1,3)-linkages that are immediately followed by β(1,4) ones. They are enzymes encoded by endo-(1,3;1,4)-β-D-glucanases genes of the glycosyl hydrolases family 17 (GH17). By contrast, MLG synthases are associated with the cellulose synthase-like F, H, and J. Recent studies with sugarcane roots have shown a strong correlation between a gradual increase in the level of endo-β-D-(1,3;1,4)-glucanases genes and proteins as aerenchyma develops into gas spaces. As in sugarcane and rice, sorghum has constitutive lysigenous aerenchyma and owns a diploid sequenced genome, differing from the complex sugarcane genome that hinders robust phylogenetic inferences. Thus, we used sorghum\'s primary roots for characterizing more in-depth molecular mechanisms involving MLG hydrolysis and aerenchyma formation. A non-branching seven-day-old primary root of sorghum allows a detailed anatomical characterization using the X-Ray microtomography technique. We divided the root into three segments (S1, S2, and S3), in which S1 has no aerenchyma, S2 is the aerenchyma initiation, and S3 a more advanced stage of aerenchyma development. Inferences indicated GH17 endo-(1,3;1,4)-β-D-glucanases utterly Poaceae-specific, family in which sorghum has three \"lichenases\" (Sblic1, Sblic2, and Sblic3) and rice two (OsEgl1 and OsEgl2). However, real-time PCR revealed differential expression solely for Sblic1, which increased tenfold from S1 to S3. Enzymatic assays with crude extracts detected an increase in endo-(1,3;1,4)-β-D-glucanases activities (S1<S2). Concomitantly, cell wall fractioning showed a decline in the relative quantity of MLG (S1>S2). To verify if a knockout at endo-(1,3; 1,4)-β-D-glucanases would compromise gas spaces development, we decided to use the CRISPR-editing tool on rice genes (OsEgl1 and OsEgl2). Our decision took into consideration the high stability for rice genetic transformation, funding time, and, above all, the mastery of rice tissue culture at Rutgers, The State University of New Jersey. OsEgl1 and OsEgl2 have shown to be expressed in roots. Both candidate genes were targeted by gRNAs, which were cloned into the rice CRISPR psgR-Cas9-Os module. Subsequently, the cassettes were subcloned into plant transformation pCAMBIA1300 vector that was used in biolistic. We transformed rice calli and submitted transformants to hygromycin selection medium. Genotyping of plants showed the presence of Cas9, although no on-target mutation has been detected by RFLP analysis, T7E1 assays, and Sanger sequencing. Notably, we acquired a T-DNA line for OsEgl2, which might be valuable transgenic material for MLG hydrolysis\' studies for an eventual loss-of- function mutation in OsEgl2. Therefore, it would aggregate significant information to our findings, leading us to assert whether MLG hydrolysis is directly involved in gas space formation. Ultimately, the higher expression of Sblic1, increase in endo-(1,3; 1,4)-β-D-glucanases activity, and decrease of relative MLG quantity are intercorrelated and, thus, we conclude that MLG is degraded in roots and possibly associated with aerenchyma formation. Lastly, we emphasize that sorghum\'s primary roots are a promising model for MLG studies and aerenchyma development.